A dependency-based study of medicine package inserts in Brazilian Portuguese - Pagano, Adriana S.; Coneglian, André V. Lopes; Silva e Oliveira, Lucas Emanuel (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2023)
This paper reports on a study of medicine package inserts (MPIs) aimed at verifying to what extent texts addressing patients evidence different morphosyntactic patterns from those addressing HC professionals. To that end, we draw on a corpus of sentences manually retrieved and aligned, which were annotated for dependency syntax following the UD guidelines. Results point to clear distinctive patterns in both sets of MPIs, which are in line with guidelines on simplified language for Brazilian Portuguese.